Electronic structure of designed [(SnSe)1+δ]m[TiSe2]2 heterostructure thin films with tunable layering sequence. Issue 12 (28th June 2019) - Göhler, Fabian; Hamann, Danielle M.; Rösch, Niels; Wolff, Susanne; Logan, Jacob T.; Fischer, Robert; Speck, Florian; Johnson, David C.; Seyller, Thomas
Abstract: Abstract : A series of [ ( SnSe )_1 + δ ]_m[ TiSe_2 ]_2 heterostructure thin films built up from repeating units of m bilayers of SnSe and two layers of TiSe2 were synthesized from designed precursors. The electronic structure of the films was investigated using X-ray photoelectron spectroscopy for samples with m = 1, 2, 3, and 7 and compared to binary samples of TiSe2 and SnSe. The observed binding energies of core levels and valence bands of the heterostructures are largely independent of m . For the SnSe layers, we can observe a rigid band shift in the heterostructures compared to the binary, which can be explained by electron transfer from SnSe to TiSe2 . The electronic structure of the TiSe2 layers shows a more complicated behavior, as a small shift can be observed in the valence band and Se3 d spectra, but the Ti2 p core level remains at a constant energy. Complementary UV photoemission spectroscopy measurements confirm a charge transfer mechanism where the SnSe layers donate electrons into empty Ti3 d states at the Fermi energy.